THE EXTRAORDINARY LIFE OF SERENA WILLIAMS - Janmohamed, Shelina; Evans, Ashley (London : Puffin, 2020)
Serena Williams began playing tennis when she was just a child, and is now an Olympic champion who's won more Grand Slam singles titles than anyone else. Throughout her life she's battled many things, from life-threatening illnesses and sports injuries to sexism and racism in the tennis world. Now she's an icon in sport, fashion and activism, an inspiration to every young person who has dared to dream big. Collect them all! Packed full of incredible stories, fantastic facts and dynamic illustrations, Extraordinary Lives shines a light on important modern and historical figures from all over the world.
Includes bibliographical references and index.
Pre-adolescent.
Keywords: Williams, Serena, -- 1981- -- Juvenile literature; Tennis players -- Biography -- Juvenile literature. -- United States; Women tennis players -- Biography -- Juvenile literature. -- United States; African American women tennis players -- Biography -- Juvenile literature. -- United States; Environmental protection -- Juvenile literature. -- Citizen participation; Climatic changes -- Juvenile literature; Biographies